The Effect of Digitalization of Accounting on Efficiency and Cost Reduction in Entrepreneurial Companies Small and Medium-Sized Enterprises in the City of Pontianak - Yiko Prayoga (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Accounting digitization is an important part of technological transformation that is believed to be able to increase the competitiveness of micro, small, and medium enterprises (MSMEs) through operational efficiency and cost control. However, empirical evidence regarding the simultaneous effect of accounting digitization on efficiency and cost reduction is still limited, especially in the regional context in Indonesia. This study aims to analyze the impact of accounting digitization on efficiency and cost reduction in MSMEs in the city of Pontianak. The study uses a quantitative approach with an explanatory survey design. Data was collected through a structured questionnaire from 372 MSME respondents selected using purposive sampling techniques, then analyzed using multiple linear regression. The results show that accounting digitization has a positive and significant effect on efficiency and cost reduction. These findings confirm that the implementation of digital accounting systems, such as cloud accounting and mobile-based accounting applications, can accelerate the recording process, improve the accuracy of reports, and reduce administrative and operational costs. Theoretically, this study reinforces the literature on the role of accounting technology in supporting the performance of MSMEs. In practical terms, the results of this study can be used as a basis for local governments and stakeholders in designing policies and digitalization assistance programs to strengthen the sustainability of MSME businesses in the digital economy era.